2006
DOI: 10.1002/ca.20346
|View full text |Cite
|
Sign up to set email alerts
|

The oblique cord of the forearm in man

Abstract: There is minimal and often conflicting data in the literature regarding the oblique cord of the forearm. The current study seeks to elucidate further the anatomy of this structure of the upper extremity. In adult cadavers, the oblique cord was observed for and, when found, measurements were made of it. Ranges of motion were carried out while observation of the oblique cord was made. An oblique cord was found on 52.6% of sides. Gantzer's muscle was found on 55% of sides and, when present, had attachment into th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 9 publications
0
8
0
1
Order By: Relevance
“…Functions of this ligament are controversial and unconfirmed. Martin 7 and Tubbs et al 8 stated in their respective cadaveric studies that the proximal oblique cord is lax in the neutral position and pronation but taut in supination. Conversely, Patel 9 reported in his study, using forelimbs of anthropoid primates, that the ligament was lax in the neutral position and supination but became taut in pronation.…”
Section: Discussionmentioning
confidence: 99%
“…Functions of this ligament are controversial and unconfirmed. Martin 7 and Tubbs et al 8 stated in their respective cadaveric studies that the proximal oblique cord is lax in the neutral position and pronation but taut in supination. Conversely, Patel 9 reported in his study, using forelimbs of anthropoid primates, that the ligament was lax in the neutral position and supination but became taut in pronation.…”
Section: Discussionmentioning
confidence: 99%
“…1992, Kapandji 2001, Moore and Dalley 2006, Tubbs et al. 2007). Thus, in the present study, forearm fractures were cast in neutral supination/pronation, contributing to effective immobilization.…”
Section: Discussionmentioning
confidence: 99%
“…The proximal oblique cord is a relatively wellinvestigated component, [13][14][15]23 whereas descriptions of this ligament are variable. Some authors 23 have insisted that the structure is a remnant or accessory head of the flexor pollicis longus muscle (Gantzer's muscle), whereas another author 13 has stated that this cord represents a thickening of the fascia overlying the supinator muscle or perhaps even a degenerate part of the supinator muscle.…”
Section: Figurementioning
confidence: 99%
“…Conflicting descriptions of function have been reported. [13][14][15] Martin 13 and Tubbs and colleagues 14 described the cord as being most taut in supination and lax in both the neutral position and pronation in human cadavers, suggesting action as a restraint on excessive supination motions. Conversely, Patel 15 reported that the proximal oblique cord became most taut in pronation rather than in supination in the forelimbs of quadrupedal primates, suggesting a possible role in maintaining elbow stability when such primates stand on their pronated forelimbs.…”
Section: Figurementioning
confidence: 99%